Perancangan Aplikasi SiCitra Menggunakan Unified Modelling Language - Wardani, Deyana Kusuma; Rahmawati, Oktavia Citra Resmi; Fatihia, Wifda Muna (Jurnal Transformatika, 2023)
Find out the live location of the family or friends that be city bus passengers is the one of city bus application users needs that hasn t been implemented yet until now, so we propose the design of software engineering that has the main feature in the form of shared live location with people that allow knowing with utilizing Unified Model Language Diagram. There are 3 (three) types of UML Diagram that have we created in this research, including Use Case Diagram, Class Diagram, and Activity Diagram. Besides that, we also produce Entity Relational Diagram and System Design to fit up the design of software engineering. Thus with modeling software before starting the development process, the system will be structured and delivered to the user as well.
Keywords: UML Diagram; Use Case Diagram; Activity Diagram; Class Diagram; Entity Relational Diagram